Sea lice infestation dataset for wild and farmed salmon populations on the Pacific coast of Canada (2001–2023) - Crawford W. Revie; Thitiwan Patanasatienkul; Gregor McEwan; Lance Stewardson (Scientific Data)
Abstract Monitoring sea lice infestation levels on populations of farmed and wild salmonids is critical to the development of evidence-based policy designed to mitigate the risk these ectoparasites represent to wild juvenile salmon and the on-going sustainability of salmon aquaculture. The data described relate to sea lice monitoring along the coast of British Columbia (BC), Canada from all areas where Atlantic salmon farms are present, spanning over two decades of observations from these farms and adjacent wild Pacific salmonid populations. Around 10,000 mean monthly sea lice estimates are included from almost 100 salmon farms spread across seven ‘fish health’ zones along the BC coast. Sea lice infestation data from over 365,000 wild hosts, observed as part of almost 17,000 sampling events in these zones, are also reported. While observations were made in the same broad geographical area, temporal coverage varies by zone. These data provide valuable insights into long-term trends, including spatial variability and demographic patterns within the sea lice populations observed on various host species along the BC coast.